Effect of pomegranate polyphenols on lipids metabolism in patients with myocardial infarction: a double-blind placebo controlled trial - Goyal, Rahul; Pathania, Monika; Nagtilak, S.; Thawani, Vijay; Jindal, Shavetika (International Journal of Research in Medical Sciences, 2019)
Background: Myocardial Infarction (MI) is a leading disease globally. Major risk factors for MI are smoking, hypertension, diabetes mellitus, reactive oxygen species (ROS), obesity, coronary artery disease (CAD) and abnormally altered blood lipid levels. It is recommended that for healthy living the risk factors for CAD and ROS should be less. Consumption of natural food supplements rich in antioxidants and polyphenols reduce the risk of MI. One herb is Pomegranate. Pomegranate is polyphenols and antioxidants rich fruit. This prompted us to find out whether the presence of antioxidants in pomegranate offers any prognostic benefits in patients with MI?. Methods: Pomegranate Extract of Whole Fruit (PEWF) was prepared as tablet of 300mg to investigate its effects in patients with MI. Total 100 participants were included in the trial. Participants were assigned to two groups of 50 each. One group received “Add On” PEWF and other got matching placebo of same colour, shape and size as comparator agent in the dose of 300mg BD for 1 month. Results: Results were compared by Z test, Chi square test and coefficient of variations. Statistical analysis proves the prognostic effect after active medication (p<0.05). Study results indicate the rejection of Null Hypothesis (H0) and acceptance of Alternative Hypothesis (H1). Conclusions: Our findings suggest that consumption of antioxidant and polyphenols rich food supplements such as PEWFs for one month reduces the risk factors for CAD.